Efektivitas Ekstrak Daun Ketapang (Terminalia Catappa L.) Sebagai Inhibitor Korosi Pada Aluminium Dalam Larutan Basa - Silaen, Fransiska Kristanti; Komalasari, Komalasari; Muria, Sri Rejeki (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Corrosion is a decrease in metal quality due to electrochemical reactions with the environment. Metals that experience a decline in quality not only involve chemical reactions but also electrochemical reactions, namely between the materials concerned with the transfer of electrons. The greater the concentration of chloride ions, the faster the corrosion process that occurs in the environment. One method of inhibiting the process of corrosion is by using a corrosion inhibitor. This study aims to determine the concentration of Terminalia catappa L. leaf extract in reducing the corrosion rate of metal, and to determine the inhibitor efficiency of Terminalia catappa L. leaf extract in reducing the rate of corrosion. This research began with the preparation of Terminalia catappa L. leaf extract using the socletation method for 12 hours with the volume ratio of ethanol solvent of aquades (1: 3). The test method in this study was the weight loss method using variations in the concentration of Terminalia catappa L leaf extract (0; 1.5; 2gr / L) with long immersion time (24, 36,48,72 hours) in a corrosive solution 0.5M NaOH. The highest corrosion rate in NaOH solution without inhibitor at 72 hours immersion time was 212.2 mpy. The results of this study showed that the greater the concentration of Terminalia catappa L leaf extract in the corrosive medium and the longer the immersion time on the aluminum plate, the smaller the corrosion rate. The highest inhibition efficiency value in the NaOH corrosion medium with a concentration of 2gr / L with a soaking time of 72 hours was 93.59%. Keywords: corrosion rate, inhibitor, terminalia catappa L leaf extract